Reinventing Liberty Nation, Commerce and the Historical Novel from Walpole to Scott - Price, Fiona (Edinburgh University Press, 2016)
Sir Walter Scott is often regarded as the first historical novelist. Reinventing Liberty challenges this view by returning us to the rich range of historical fiction written in the late 18th and early 19th century. For the first time placing these works in the context of British politics and British history writing, this book redefines the historical novel, revealing a genre which seeks to manage political change through historiographical experimentation. It explores how historical novelists participated in a contentious debate concerning the nature of commercial modernity, the formulation of political progress and British national identity. Ranging across well-known writers, like William Godwin, Horace Walpole and Frances Burney, to lesser-known figures, such as Cornelia Ellis Knight and Jane Porter, Reinventing Liberty uncovers how history becomes a site to rethink Britain as "land of liberty." Reading Scott in relation to this tradition, Reinventing Liberty demonstrates the genre's troubled role in the construction of the myth of Britain as a nation of gradual, safe political change.
Description based on print version record.
Knowledge Unlatched Round 2
Keywords: Political Science; Political science; Electronic books